Обґрунтування методів оцінки розвитку виробництва і ефективності інвестицій - Крамськой, Дмитро Юрійович (НТУ"ХПІ", 2016)
Удосконалено динамічний метод оцінки економічності виробництва на основі обліку основних засобів не за первісною, а за залишковою вартістю. Запропоновано нові показники оцінки ефективності інвестицій з врахуванням економічності розвитку виробництва: середньозважена частка дисконтованого прибутку, коефіцієнт ресурсної економічності виробництва, що підлягає інвестуванню, а також проведено ранжування показника ресурсної економічності виробництва для можливості оцінки проекту за відсутності альтернативного.

Improved dynamic efficiency evaluation method based on production of fixed assets not original, and the residual value. We propose new indicators to measure the effectiveness of investments, taking into account the development of production efficiency: average proportion of the discounted profit rate resource efficiency of production is subject to investment, as well as conducted a ranking index of the resource production efficiency for the project evaluation in the absence of alternative possibilities. They allow you to overcome a certain one-sidedness of the existing system of evaluation of investment projects by attracting a field of analysis parameters that directly characterize the quality of the invested production.
Justification evaluation methods of production and investment efficiency
Keywords: інвестиційна діяльність; інвестиційний проект; дисконтований прибуток; економічність виробництва; investment; investment project; present value; cost of production